Design and development of optical fiber Bragg grating based device for measurement of handgrip force - Jahan, M. A. Ibrar; Chethana, K.; Honnungar, Rajini V.; Asokan, S. (Optical and quantum electronics, 2022)
A non-invasive optical fiber Bragg grating based handgrip device for the dynamic measurement of the handgrip force is proposed. The handgrip force is an indicator of biomechanical parameters like fracture of vertebral bones, limb strength, etc. The proposed device converts the grip force exerted at the surface into strain variation on the vertical bars, which is sensed by the bonded fiber Bragg grating sensors. Ansys Multiphysics is used for modeling and analysis of the handgrip device. The developed device is calibrated using a micro universal testing machine (μUTM) to determine the relationship between the load/force applied on the device and the Bragg wavelength shift of the fiber Bragg grating sensor and a calibration factor of 5.35 µϵ/Kg is obtained. The device shows a sensitivity of 1.21 pm/μϵ. The developed device is used to measure the handgrip force of a subject with a fractured arm. 10 volunteers (both men and women) with fractured arms were involved in the study. Additionally, the fiber Bragg grating based handgrip device is clinically evaluated in comparison to an X-ray image. The radiations due to X-rays harm the healthy tissues, concerning this developed device offers benefits such as being immune to electromagnetic interference, small size, lightweight, highly sensitive and applicable for a variation in the force exerted by the handgrip, aiding in monitoring the rehabilitation of patients with arm injuries.